Nutritional value of sugarcane varieties in relation to nitrogen fertilization for the pre-Amazon Region of Brazil - Mayanna Karlla Lima Costa (Semina: Ciências Agrárias, 2017)
This study evaluated the nutritional value of sugarcane varieties in relation to nitrogen fertilization. The varieties studied were RB 863129, RB 867515, and RB 92579, and nitrogen fertilizer was applied at doses of 0, 60, 80, 120, and 140 kg N ha-1. The experiment was divided into two stages: i) Year I – plant cane, when the yield and nutritional quality of the three sugarcane varieties were evaluated; ii) Years II and III, when and the effect of nitrogen fertilization on the nutritional quality of the first and second ratoon crops of the same varieties was evaluated. In plant cane the yield (t ha-1) and DM (dry matter) and CP (crude protein) contents were higher for the RB 863129 variety. There was no difference between the varieties regarding their NDF (neutral detergent fiber) and ADF (acid detergent fiber) contents and IVDMD (in vitro dry matter digestibility). In the first and second ratoon crops, there was a difference between the varieties and fertilizer doses for the evaluated parameters, with the exception of the DM content and IVDMD, which were influenced by the varieties, doses of N, and cutting years. The RB 92579 variety showed the best yield of the two ratoon crops (131 t ha-1 of stems) and the best nutritional parameters (26% ADF, 41% NDF, 2.4% CP, and 69.4% IVDMD). The sugarcane yield and its nutritional quality can be influenced by the cutting year and nitrogen fertilization management system and by the variety type